Immunoregulatory Effects of Mitochondria Transferred by Extracellular Vesicles - She, Zhou; Xie, Min; Hun, Marady; Abdirahman, Amin Sheikh; Li, Cuifang; Wu, Feifeng; Luo, Senlin; Wan, Wuqing; Wen, Chuan; Tian, Jidong (Frontiers in Immunology, 2021)
Mitochondria participate in immune regulation through various mechanisms, such as changes in the mitochondrial dynamics, as metabolic mediators of the tricarboxylic acid cycle, by the production of reactive oxygen species, and mitochondrial DNA damage, among others. In recent years, studies have shown that extracellular vesicles are widely involved in intercellular communication and exert important effects on immune regulation. Recently, the immunoregulatory effects of mitochondria from extracellular vesicles have gained increasing attention. In this article, we review the mechanisms by which mitochondria participate in immune regulation and exert immunoregulatory effects upon delivery by extracellular vesicles. We also focus on the influence of the immunoregulatory effects of mitochondria from extracellular vesicles to further shed light on the underlying mechanisms.